1999
DOI: 10.1021/js980419b
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of aqueous and lipid solubilities with flux for prodrugs of 5‐fluorouracil, theophylline, and 6‐mercaptopurine: A potts–Guy approach

Abstract: The Potts and Guy equation that has been used to predict permeability coefficients for molecules being delivered from aqueous vehicles has been transformed to accommodate lipid vehicles that are less polar than skin, and polar vehicles that are less polar than water. Solubilities in pH 4.0 aqueous buffer (SAQ), solubilities in isopropyl myristate (SIPM), and molecular weights (MW) of prodrugs of 5-fluorouracil (5-FU), theophylline (Th), and 6-mercaptopurine (6-MP) have been regressed against their fluxes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…1) where n=42 (6). The coefficients to the IPM and aqueous solubility parameters were approximately equal, which supported the previous observations (4,5) that a balance of improved lipid and aqueous solubilities was important to optimize flux from a lipid vehicle.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…1) where n=42 (6). The coefficients to the IPM and aqueous solubility parameters were approximately equal, which supported the previous observations (4,5) that a balance of improved lipid and aqueous solubilities was important to optimize flux from a lipid vehicle.…”
Section: Introductionsupporting
confidence: 85%
“…The synthesis of alkyloxycarbonyl-Th derivatives (4)(5)(6) involves the acylation of Th-H with alkyoxycarbonyl chlorides in presence of mild base, TEA, and DCM as the solvent (Scheme 2). The synthesis of alkyloxycarbonyl chlorides from commercially available alcohols, i.e., MEA, MDEA, or MPA involves the conversion of the alcohol to a chloroformate by reaction with triphosgene and pyridine in DCM as the solvent as reported by us before (14).…”
Section: General Synthesis Of 4-6mentioning
confidence: 99%
See 1 more Smart Citation
“…9 The MO solubilties (S MO ) have been converted to units of mM. Although the partition coef®cients (K MO:AQ ) for the distribution of unionized NSAIDS between MO and acidic water (we will use AQ instead of W*) were measured, their values were not reported.…”
Section: Methodsmentioning
confidence: 99%
“…1 Sloan and co-workers 2±8 have published numerous articles on the delivery of theophylline, 5-¯uorouracil, and 6-mercaptopurine from suspensions of their prodrugs in isopropyl myristate (IPM) through hairless mouse skin under essentially identical conditions. For this data set, Roberts and Sloan 9 have shown that the transformed Potts±Guy equation, which speci®cally makes it possible to predict¯ux from lipid vehicles, shows a large positive dependence of ux on the aqueous solubilities (S AQ ) as well as the solubilities in IPM (S IPM ) of the prodrugs that comprise the data set. This result is not consistent with previous results that suggested that the solubility properties of the skin barrier are most accurately modeled by octanol alone.…”
Section: Introductionmentioning
confidence: 97%